(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The standard treatment for non-muscle-invasive bladder cancer (NMIBC) is transurethral resection of the tumour (TURBT) with adjuvant intravesical instillation therapy, as indicated by the tumor's risk of recurrence and progression. Despite adequate treatment, two-thirds of patients will have an intravesical recurrence, and one in every five will progress to muscle-invasive disease (MIBC) [3-a5]. Materials and Methods: Data were analysed from 55 consecutive patients who were newly diagnosed with NMIBC using magnetic resonance imaging (MRI) scanning and diffusion-weighted imaging (DWI), as well as cystoscopic examinations, and were treated between January 2021 and December 2021. These patients received either conventional TURBT and simultaneous chemotherapy (n=22) or surrounding en bloc TURBT and simultaneous intravesical chemotherapy (n=33). Primary NMIBC diagnosed with cystoscopic examination and MRI scanning, as well as a tumour diameter of 0.5-4.0 cm, were inclusion criteria. Results: The surrounding en bloc TURBT was performed on 33 patients, while conventional TURBT was performed on 22 patients. There were no significant differences between the two groups in demographics, age, tumour diameter, number of tumours, T stage, or grade (p > 0.05). In the surrounding en bloc TURBT group, 18 (54.5%) of 33 patients had a single lesion, while 13 (60.0%) of 22 patients in the conventional TURBT group had a single lesion. Multiple lesions were discovered in 15 (45.5%) of 33 patients and 9 (40.0%) of 22 patients. The tumor diameter ranged from 0.5 to 4.4 cm (2.25 ± 0.96 cm) in the surrounding en bloc group and 0.8 to 4.5 cm (1.91 ± 0.95 cm) in the conventional group, and there was no statistically significant difference in tumor diameter between the two groups. Conclusion: The findings of this study suggest that urologists can widely use surrounding en bloc TURBT and simultaneous intravesical therapy with a general bipolar electrode loop. It will help most patients with NMIBC reduce recurrence, even if they have T1 bladder cancer. The innovative strategy was feasible, effective, and risk-free. We believe that en bloc TURBT combined with concurrent chemotherapy will become the new standard for treating NMIBC in the future.